Pengawetan Kayu Karet Menggunakan Asap Cair dan Ekstrak Kunyit dengan Teknik Perendaman Dingin - Sherly Hanifarianty; Afrizal Vachlepi (Widyariset, 2019)
Rubber wood (Hevea brasiliensis) is a wood with low durability wood. In general, rubber wood is preserved by chemicals which are relatively not environmental friendly. This study was conducted to evaluate the potential of liquid smoke from pyrolysis of palm oil kernel and turmeric extract as wood preservatives. Rubber wood was soaked in 5% w/v of liquid smoke and turmeric extract, respectively for 2, 8, and 14 days which preservation was carried out for six months. Formaline and boric acids was used for comparison as well. The used parameters were preservative retention, moisture content during storage, color changes, and damage level. The results indicated that the longer the immersion, the greater the preservative retention and water content. Turmeric extract and liquid smoke provided a brownish yellow and light brown color. In general, liquid smoke for two days of immersion adequate for six months preservation whereas turmeric acid for two months.